Myelopathy secondary to an intramedullary arteriovenous malformation in a mature dog. (1st February 2021) - De Freitas, Maria Ines; Housley, Daniel; Caine, Abby; Fauchon, Emilie; Baiker, Kerstin; Corbetta, Davide; Cherubini, Giunio B
Abstract: A 2‐year‐old crossbreed dog was presented for evaluation of a 6‐week history of progressive paraparesis. Magnetic resonance imaging and computed tomography angiography of the thoracic and lumbar spinal cord disclosed multifocal, anomalous, small, vascular structures, distributed throughout the subarachnoid space of the included section of the spinal cord. An additional focal intramedullary lesion was identified extending from T9 to T10 to T12. Histopathological examination confirmed the presence of an intramedullary arteriovenous malformation affecting the thoracic spinal cord and leading to diffuse congestion and focal hemorrhages into the affected spinal cord.